THE IMPACT OF ORGANIZATIONAL BEHAVIORS ON COMPANY GOALS OF MANUFACTURING INDUSTRY IN CHINA - Dong Yiqi; Wan Aishah Wan Mohd Nowalid (International Journal of Accounting, Finance and Business, 2024)
This research delves into how organizational behaviors influence the attainment of corporate objectives in the distinctive setting of the manufacturing sector in China. Using a positivist research approach, this study will delve into the intricate dynamics between leadership styles, strategies to motivate employees, and the organizational culture's role in shaping the success of an organization. The results underscore the importance of transformational leadership, maintaining a balance between intrinsic and extrinsic motivation, nurturing a clan culture, and aligning goals to drive performance and goal achievement.